2015
DOI: 10.1186/s13034-015-0077-0
|View full text |Cite
|
Sign up to set email alerts
|

Positive parenting: a randomised controlled trial evaluation of the Parents Plus Adolescent Programme in schools

Abstract: BackgroundThe aim of this study was to evaluate the Parents Plus Adolescents Programme (PPAP)—a parent training course specifically targeting parents of young adolescents (aged 11–16 years)—when delivered as a preventative programme in community school settings.MethodsA sample of 126 parents (mean age of children = 12.34 years; range = 10–16 years) were randomly assigned to either a treatment (PPAP; n = 82) or a waiting-list control condition (WC; n = 44). Analyses are based on a study-completer sample post-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…In a randomized controlled trial of the PP Adolescents Program offered to families of normal adolescents attending regular secondary schools in a rural community, Nitsch et al. () found that compared with the waiting list control group, after treatment the PP Adolescent Program group showed significantly greater improvement on a range of measures. These gains were maintained at follow‐up.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a randomized controlled trial of the PP Adolescents Program offered to families of normal adolescents attending regular secondary schools in a rural community, Nitsch et al. () found that compared with the waiting list control group, after treatment the PP Adolescent Program group showed significantly greater improvement on a range of measures. These gains were maintained at follow‐up.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies in the meta‐analysis were underpowered. The sample size in only five studies (Gerber et al., ; Hayes et al., ; Keating et al., ; Lonergan et al., ; Nitsch, Hannon, Rickard, Houghton, & Sharry, ) was sufficient to provide adequate power ( p = .05, β = .80) to detect a small to moderate effect size, which is what has been reported in meta‐analyses of other parenting programs (Menting et al., ; Sanders et al., ).…”
Section: Characteristics Of Pp Evaluation Studiesmentioning
confidence: 87%
See 2 more Smart Citations
“…As previous research into the PPAP and WTO programmes has shown the efficacy of both programmes in clinical settings (e.g. Beattie et al, 2007;Nitsch, 2011), this study was concerned more with the effective delivery of these programmes in a novel setting, and so the positive findings in relation to adolescent and parent outcomes are encouraging. Due to the number of different sites the study was conducted across, the findings of the study are also more readily generalisable and thus provide relatively robust evidence for the effectiveness of the intervention.…”
Section: Strengths and Limitationsmentioning
confidence: 82%